Răspuns :
a + b + c = 363
a = b + 97
b = 3c
a = 3c + 97
3c + 97 + 3c + c = 363
7c = 363 - 97
7c = 266
c = 266 : 7
c = 38
a = 3c + 97
a = 3 x 38 + 97
a = 114 + 97
a = 211
b = 3c
b = 3 x 38
b = 114
verificam
211+ 114 + 38 = 363
a = b + 97
b = 3c
a = 3c + 97
3c + 97 + 3c + c = 363
7c = 363 - 97
7c = 266
c = 266 : 7
c = 38
a = 3c + 97
a = 3 x 38 + 97
a = 114 + 97
a = 211
b = 3c
b = 3 x 38
b = 114
verificam
211+ 114 + 38 = 363
a + b + c = 363
a = b + 97
b = 3c
a = 3c + 97
3c + 97 + 3c + c = 363
7c = 363 - 97
7c = 266
c = 266 : 7
c = 38
a = 3c + 97
a = 3 x 38 + 97
a = 114 + 97
a = 211
b = 3c
b = 3 x 38
b = 114
V:211+ 114 + 38 = 363
a = b + 97
b = 3c
a = 3c + 97
3c + 97 + 3c + c = 363
7c = 363 - 97
7c = 266
c = 266 : 7
c = 38
a = 3c + 97
a = 3 x 38 + 97
a = 114 + 97
a = 211
b = 3c
b = 3 x 38
b = 114
V:211+ 114 + 38 = 363